The Application of Picture Word Inductive Model (PWIM) in Teaching Writing Recount Text - I Dewa Ayu Inten Dwi Cahyani (English Education Department at FKIP Nommensen University, 2023)
As the last stage of language learning, many students have difficulty mastering writing skills. Likewise, at SMPN 1 Tembuku where the eighth-grade students in the second semester have problems in writing, especially writing recount text. Thus, Picture Word Inductive Model can be used as an alternative strategy in teaching writing and overcome the difficulties mentioned to explore whether applying PWIM has an effect on students’ skill in writing recount text. A quasi-experimental with posttest only control group design was used as the research design. The result of data analysis showed that the experimental group mean score was 76.09, while the control group mean score was 72.25. It showed that the mean score of experimental group was higher than the mean score in control group as well as the effect size calculation was in medium category with the result 0.651. Thus, there was significant effect of using Picture Word Inductive Model on students’ skill in writing recount text. PWIM helped students in writing process and make students easier generate their ideas well into writing. Therefore, it was suggested to use PWIM as an alternative strategy in teaching writing.